2002
DOI: 10.1073/pnas.092657699
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine in vivo inhibitory effects of hepatitis B virus X protein (HBx) on liver cell proliferation: An alternative mechanism of HBx-related pathogenesis

Abstract: The role of the hepatitis B virus X protein (HBx) in the pathogenesis of hepatitis B virus (HBV) infection remains unclear. HBx exhibits pleiotropic biological effects, whose in vivo relevance is a matter for debate. In the present report, we have used a combination of HBx-expressing transgenic mice and liver cell transplantation to investigate the in vivo impact of HBx expression on liver cell proliferation and viability in a regenerative context. We show that moderate HBx expression inhibits liver regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 73 publications
3
46
2
Order By: Relevance
“…However, HBx might exert deleterious activities and perhaps induce genomic instability at later stages of the infection, and thereby contribute to liver cancer development, when hepatocytes actively divide to replace those destroyed by the host immune response. This is consistent with HBx inhibiting liver regeneration after partial hepatectomy in transgenic mice, 36 and it may explain the higher rate of chromosomal abnormalities observed in HCC caused by HBV as compared with other causative agents. 37 Because both activities require the binding of HBx to DDB1, this HBV-host protein interaction may represent a promising new target for therapeutic intervention.…”
supporting
confidence: 70%
“…However, HBx might exert deleterious activities and perhaps induce genomic instability at later stages of the infection, and thereby contribute to liver cancer development, when hepatocytes actively divide to replace those destroyed by the host immune response. This is consistent with HBx inhibiting liver regeneration after partial hepatectomy in transgenic mice, 36 and it may explain the higher rate of chromosomal abnormalities observed in HCC caused by HBV as compared with other causative agents. 37 Because both activities require the binding of HBx to DDB1, this HBV-host protein interaction may represent a promising new target for therapeutic intervention.…”
supporting
confidence: 70%
“…Our conclusions are consistent with previous results in which HBx induced proliferation in cultured cells [27] and another study in which HBx expression induced cell-cycle progression within the milieu of the regenerating liver [28]. The results of our study oppose the conclusions of other studies that showed that transient transfection of HBx induced apoptosis and that HBx inhibited hepatocyte regeneration [29][30][31]. The reasons behind this apparent discrepancy need to be further investigated.…”
Section: -Test)contrasting
confidence: 56%
“…HBx can act as a co-transactivator to induce cell apoptosis and inhibit the proliferation of liver cells during the development of HCC. 25,26 Our observations that HBsAg knock-in transgenic mice developed HCCs 3 months earlier than HBx transgenic mice demonstrated that HBsAg also plays an important direct role in the development of HBV-related HCC though a mechanism different than that of HBx. We noticed that only male HBsAg gene knock-in transgenic mice between the ages of 15 and 24 months developed HCCs.…”
Section: Discussionmentioning
confidence: 94%